Hanging-associated left ventricular systolic dysfunction. (March 2015) - Jin, Uram; Park, Jin-Sun; Min, Young-Gi; Yang, Hyoung-Mo; Lim, Hong-Seok; Choi, Byoung-Joo; Choi, So-Yeon; Yoon, Myeong-Ho; Hwang, Gyo-Seung; Tahk, Seung-Jea; Shin, Joon-Han
Abstract: Backgrounds : Although hanging injury is infrequent, its clinical course is usually devastating. Hanging patients usually need cardiopulmonary resuscitation (CPR). However, hanging-associated cardiovascular damage has not been fully established. The aim of this study was to evaluate echocardiographic findings in patients with hanging injury. Methods : We enrolled 25 patients (nine males and 16 females with mean age of 33 ± 15 years) with hanging injury. Echocardiography was performed within 2 weeks after admission. Clinical, demographic, and laboratory data as well as transthoracic echocardiographic findings were analyzed. Results : Of the 25 patients, eight (two males and six females with mean age of 34 ± 13 years) showed left ventricular systolic dysfunction (LVSD). Mean LV ejection fraction was 34 ± 16%. Global hypokinesia was present in one patient. Apical ballooning with sparing of the basal segment was present in two patients. Basal akinesia and apical hyperkinesia were present in one patient. Four patients showed regional wall motion abnormalities unmatched with coronary territories. The duration of suspension or CPR was not significantly different according to the presence of LVSD. Conclusion : This study showed the echocardiographic findings in considerable numbers of patients with hanging injury for the first time. Variable patterns of LVSD were present in patients with hanging injury.